WHEN TASTE IS NOT ENOUGH: DETERMINANTS OF CUSTOMER LOYALTY IN GEROBAKMIE, A LOCAL CULINARY BUSINESS IN JAMBI CITY - Ramadhan, Raihan Fajri; Sabrina, Hanan Laras; Wilona, Zora Anjas (Journal of Business Studies and Management Review, 2026)
This study examines the effect of location, service quality, and product quality on customer loyalty at Gerobakmie, a local culinary business in Jambi City. Customer loyalty is a critical issue for local food businesses because intense competition requires firms to retain customers through more than product taste alone. A quantitative survey approach was employed, involving 240 Gerobakmie customers selected through purposive sampling. Data were collected using an online questionnaire and analyzed through validity and reliability tests, classical assumption tests, and multiple linear regression. The findings show that location, service quality, and product quality have positive and significant effects on customer loyalty, both partially and simultaneously. Service quality has the strongest influence, followed by product quality and location. The model explains 63.6% of the variation in customer loyalty, indicating that these three variables are important determinants of repeat purchase, customer recommendation, and emotional attachment. The results suggest that customer loyalty in local culinary businesses is shaped not only by taste, but also by accessibility, responsive service, and consistent product quality. Practically, Gerobakmie should improve service reliability, maintain taste consistency, strengthen product standardization, and enhance location-related convenience such as visibility and parking access. This study contributes to marketing management literature by providing empirical evidence on customer loyalty formation in a local culinary business context